2013
DOI: 10.1002/jgrb.50182
|View full text |Cite
|
Sign up to set email alerts
|

Multiple transition zone seismic discontinuities and low velocity layers below western United States

Abstract: [1] With P-to-S converted waves recorded at seismic stations of the U.S. Transportable Array, we image the fine structure of upper mantle and transition zone (TZ) beneath the western U.S. We map the topographies of seismic discontinuities by stacking data by common conversion points along profiles. Systematic depth and amplitude measurements are performed not only for the well-known "410" and "660" interfaces but also for minor seismic discontinuities identified around 350, 590, and 630 km depths. The amplitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
75
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 68 publications
(84 citation statements)
references
References 89 publications
(202 reference statements)
9
75
0
Order By: Relevance
“…7d). We checked by making seismic phase diagrams restricted to the eastern or western regions relative to the Nevada/Utah borders, that the characteristics of our observations in Tauzin et al (2013) are preserved. We observe the '350' in both eastern and western regions with stronger amplitudes in the west, the negative '590' mostly in the east, and the positive '620' in both areas.…”
Section: Seismically Deduced Phase Diagramsmentioning
confidence: 85%
See 4 more Smart Citations
“…7d). We checked by making seismic phase diagrams restricted to the eastern or western regions relative to the Nevada/Utah borders, that the characteristics of our observations in Tauzin et al (2013) are preserved. We observe the '350' in both eastern and western regions with stronger amplitudes in the west, the negative '590' mostly in the east, and the positive '620' in both areas.…”
Section: Seismically Deduced Phase Diagramsmentioning
confidence: 85%
“…As an example, the initial section for a profile at 41 • N is corrected from the shallow heterogeneity and the temperature induced velocity changes and leads to a profile where the signal should be only due to the true interface undulations. Tauzin et al (2013) reported the presence of seismic discontinuities around 350, 590 and 620 km depths in the mantle below western US. These features are more local than the '410' and '660' but appear anyway in the diagram of Fig.…”
Section: Seismically Deduced Phase Diagramsmentioning
confidence: 97%
See 3 more Smart Citations